Magnetohydrodynamic turbulence and turbulent dynamo in partially ionized plasma - Siyao Xu; A Lazarian (New Journal of Physics, 2017)
Astrophysical fluids are turbulent, magnetized, and frequently partially ionized. As an example of astrophysical turbulence, the interstellar turbulence extends over a remarkably large range of spatial scales and participates in key astrophysical processes happening on different ranges of scales. Significant progress has been achieved in the understanding of the magnetohydrodynamic (MHD) turbulence since the turn of the century, and this enables us to better describe turbulence in magnetized and partially ionized plasmas. In fact, the modern revolutionized picture of MHD turbulence physics facilitates the development of various theoretical domains, including the damping process for dissipating MHD turbulence and the dynamo process for generating MHD turbulence with many important astrophysical implications. In this paper, we review some important findings from our recent theoretical works to demonstrate the interconnection between the properties of MHD turbulence and those of turbulent dynamo in a partially ionized gas. We also briefly exemplify some new tentative studies on how the revised basic processes influence the associated outstanding astrophysical problems in areas such as magnetic reconnection, cosmic ray scattering, and magnetic field amplification in both the early and present-day universe.